Tuning of the properties of a picolinic acid-based bispidine ligand for stable copper(II) complexation - Comba, Peter; Jakob, Maik; Rück, Katharina; Wadepohl, Hubert (Inorganica chimica acta, 2018)
The synthesis of the hexadentate bispidine-picolinate ligand L with two tertiary amine, two para-methoxy-substituted pyridine donors (p-OMe) and a picolinate group is reported, together with its NiII, CoII, CuII and ZnII coordination chemistry. The X-ray crystal structures of the CuII and ZnII complexes confirm that the geometries are very similar to those of the unsubstituted ligand. The increased nucleophilicity of the p-OMe substituted pyridine groups leads to a significant decrease in the metal-pyridine bond length but, due to the rigidity of the adamantane-derived bispidine backbone, the other metal-donor bonds are slightly elongated, and this leads to a larger degree of axial distortion, which augments the preference of the ligand for the Jahn-Teller-active CuII center. The structural effects are supported by the dd-electronic and EPR spectra, which indicate that, for CoII, NiII and CuII, the overall ligand field strengths of the unsubstituted ligand L′ and the p-OMe-substituted derivative L are very similar, and for CuII the in-plane ligand field is significantly stronger for the p-OMe-substituted ligand L. The MII/I redox potentials with the optimized ligand L are generally more negative for the CoII, NiII and CuII complexes, indicating that the oxidized form of the complexes takes more profit of the increase in complex stability. For CuII this is analyzed on the basis of the potentiometrically determined stability constants and their correlation with the redox potentials of the substituted and unsubstituted bispidines together with a large series of published data with other ligand systems. It emerges that L is a very selective CuII ligand with a great potential for radiopharmaceutical applications.